Natural stone heat preservation and decoration integrated plate based on foaming ceramic and preparation method thereof

By using the combination technology of foamed ceramics and natural stone in the insulation and decorative integrated panel, combined with specific raw material preparation and process processing, the problem of difficult balance between thermal insulation, impact resistance and fire resistance of existing panels is solved, which is significantly Improves product stability and performance.

CN119466249AActive Publication Date: 2025-02-18XINJIANG PROD & CONSTR CORPS CONSTR ENG SCI & TECH RES INST CO LTD +1

Patent Information

Application Number
CN202411740650.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing thermal insulation decorative integrated panels are difficult to balance and coordinate between thermal insulation, impact resistance and fire resistance, and have poor stability in water, acid, corrosion and hot and cold cycles.

Method used

The natural stone insulation decorative integrated panel is adopted based on foamed ceramics. By blending raw materials such as quartz, clay, fly ash in the base layer with glass microbeads, flame retardants, dispersants and foaming agents, it combines and balances the effect. The combination of the agent and the toner that blends the talc powder modified form a sheet with excellent properties.

Benefits of technology

The balance and coordination between thermal insulation, impact resistance and fire resistance of the thermal insulation decorative integrated panel is achieved, and the product's water resistance, acid corrosion and hot and cold cycle stability is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162543230000131
    Figure BDA0005162543230000131
  • Figure BDA0005162543230000151
    Figure BDA0005162543230000151
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation decorative plates. A base body layer is prepared from the following raw materials in parts by weight: 25 to 30 parts of quartz, 10 to 15 parts of clay, 8 to 12 parts of fly ash, 7 to 11 parts of a binding and balancing agent, 6 to 9 parts of a talc powder modified tonality agent, 5 to 8 parts of glass beads, 4 to 7 parts of a flame retardant, 2 to 4 parts of a dispersing agent, 1 to 3 parts of a foaming agent and 20 to 25 parts of deionized water. The thermal insulation and decoration integrated board is prepared by matching the base body layer with the facing layer, the base body layer is prepared by blending and coordinating quartz, clay and fly ash with glass beads, a flame retardant, a dispersing agent and a foaming agent, and the added coupling and balancing agent and the added adjusting agent modified by blended talcum powder are matched and jointly synergic, so that the thermal insulation and decoration integrated board is prepared. The thermal insulation property, the impact resistance and the fire resistance of the product are improved in a balanced and coordinated manner, and meanwhile, the product has remarkable water resistance, acid corrosion resistance and thermal cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation decorative panels, and in particular to a natural stone thermal insulation decorative integrated panel based on foamed ceramics and a preparation method thereof. Background Art

[0002] With the development of economy, people's living standard has improved, and the requirement for quality of life has been rising year by year. Wall insulation decoration materials are emerging decorative materials in recent years. Foamed ceramic insulation decorative panels are panels with foamed ceramic as the base and decorative patterns on the surface. They have the integrated effect of insulation and decoration. They are mainly used for the insulation decoration of the exterior walls of buildings.

[0003] In order to improve the thermal insulation performance of the existing thermal insulation decorative integrated panels, it is easy to make it difficult to balance the thermal insulation, impact resistance and fire resistance of the products. At the same time, the products have poor resistance to water, acid corrosion and cold and hot cycle stability, which limits the use efficiency of the products. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a natural stone thermal insulation and decorative integrated board based on foamed ceramics and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a natural stone thermal insulation decorative integrated board based on foamed ceramics, comprising a base layer and a finishing layer, wherein the finishing layer has a decorative pattern on its surface for decorating the base layer, and the base layer comprises the following raw materials in parts by weight:

[0007] 25-30 parts of quartz, 10-15 parts of clay, 8-12 parts of fly ash, 7-11 parts of linking and balancing agents, 6-9 parts of talcum powder modified conditioning agent, 5-8 parts of glass beads, 4-7 parts of flame retardant, 2-4 parts of dispersant, 1-3 parts of foaming agent, and 20-25 parts of deionized water.

[0008] Preferably, the natural stone thermal insulation decorative integrated board comprises the following raw materials in parts by weight:

[0009] 27.5 parts of quartz, 12.5 parts of clay, 10 parts of fly ash, 9 parts of linking and balancing agent, 7.5 parts of talcum powder modified conditioning agent, 6.5 parts of glass beads, 5.5 parts of flame retardant, 3 parts of dispersant, 2 parts of foaming agent, and 22.5 parts of deionized water.

[0010] Preferably, the dispersant is sodium lignin sulfonate; the foaming agent is silicon carbide; and the flame retardant is magnesium hydroxide.

[0011] Preferably, the preparation method of the linking and balancing agent is:

[0012] S01: adding nano-yttrium oxide to a 5% chitosan solution with a mass fraction of 2 to 5 times the total amount of nano-yttrium oxide, and then adding a 4% sodium silicate solution with a mass fraction of 5 to 8% of the total amount of nano-yttrium oxide, stirring thoroughly to obtain an additive solution;

[0013] S02: The mesoporous silica is added to a sufficient amount of a 5% by mass sulfuric acid solution and stirred sufficiently, then washed with water and dried, and the dried mesoporous silica and the additive solution are stirred sufficiently in a weight ratio of 2:5 to obtain a mesoporous silica liquid;

[0014] S03: The mesoporous silica liquid and the linking and balancing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the linking and balancing agent.

[0015] Preferably, the particle size of the mesoporous silica is between 70 and 80 nm, and the pore size is between 15 and 20 nm.

[0016] Preferably, the preparation method of the balancing agent is:

[0017] 4 to 7 parts of glass fiber, 1 to 3 parts of stearic acid and 5 to 8 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent;

[0018] 3-5 parts of boron nitride agent are added into 5-8 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

[0019] Preferably, the preparation method of the talc-modified conditioning agent is:

[0020] S01: Stir talc powder thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry, stir the dried talc powder thoroughly in a sodium citrate solution of 3 to 5 times the total amount of the dried talc powder to obtain a talc powder liquid;

[0021] S02: 5 to 8 parts of talc liquid, 2 to 4 parts of silane coupling agent KH550, 1 to 3 parts of sodium hexametaphosphate and 1 to 2 parts of 5% by mass sodium lignin sulfonate solution are fully blended to obtain a talc blending agent;

[0022] S03: adding 3-5 parts of a-alumina and 2-3 parts of montmorillonite powder to 5-8 parts of dopamine hydrochloride solution, and then adding 1-2 parts of sodium carboxymethyl cellulose for ultrasonic treatment, and then filtering and drying to obtain a-alumina-montmorillonite property-adjusting hybrid agent;

[0023] S04: The talcum powder conditioning agent and the α-alumina-montmorillonite conditioning hybrid agent are mixed and ball-milled in a weight ratio of 5:(2-3) at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the conditioning agent modified by the talcum powder is filtered and dried to obtain.

[0024] Preferably, the mass fraction of the sodium citrate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

[0025] Preferably, the ultrasonic power of the ultrasonic treatment is 450-500W, and the ultrasonic time is 15-20min.

[0026] The present invention also provides a method for preparing a natural stone thermal insulation decorative integrated board based on foamed ceramics, comprising the following steps:

[0027] The raw materials in the base layer are mixed and ball-milled thoroughly at a mixing speed of 1500r / min for 1h, and then put into a mold for pressing at a pressing pressure of 10-15MPa for 20min. After the pressing is completed, the mold is demoulded to obtain a green body, and the green body is sintered at 1150-1170℃ for 2h. After the sintering is completed, the base layer is obtained, and then the surface of the base layer is decorated with a pattern to form a finishing layer to obtain the thermal insulation decorative integrated board of the present invention.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The thermal insulation decorative integrated board of the present invention is made of a base layer and a facing layer. The base layer is blended and coordinated by quartz, clay, fly ash, glass microbeads, flame retardant, dispersant and foaming agent, and the added linking and balancing agent and the modifier modified by blending talcum powder are coordinated and coordinated. The thermal insulation, impact resistance and fire resistance of the product are balanced and coordinated, and the product has remarkable effects on water resistance, acid corrosion and cold and hot cycle stability; the linking and balancing agent is made by ball milling improvement of mesoporous silica liquid and linking and balancing agent. The mesoporous silica in the mesoporous silica liquid is activated and improved by acid solution, and then stirred and adjusted by adding liquid. The nano yttrium oxide in the added liquid is coordinated with chitosan solution and sodium silicate solution. The mesoporous silica has a porous high specific surface area. The active efficiency of the mesoporous silica is enhanced by the coordination of raw materials such as nano yttrium oxide in the added liquid. At the same time, the coordination of the linking and balancing agent is enhanced to improve the performance effect of the product. The glass fiber in the linking and balancing agent is adjusted with lanthanum nitrate solution to enhance the glass fiber. The invention discloses an active effect, and at the same time, the glass fiber is mixed into the pores of mesoporous silica with a needle-like structure, and is co-loaded into the system through the mesoporous silica to enhance the interface and connectivity of the system and optimize the performance effect of the product. At the same time, the coordination between the boron nitride and the zinc nitrate solution is further coordinated with the glass fiber liquid to enhance the performance stability of the system; the talc in the talc-modified conditioning agent is activated and improved by a hydrogen peroxide solution, and is dispersed and adjusted with a sodium citrate solution, and at the same time, an a-alumina-montmorillonite conditioning hybrid agent is coordinated, and the a-alumina and montmorillonite powder in the a-alumina-montmorillonite conditioning hybrid agent are used as the matrix material, and the reinforcing talc is coordinated. Through the coordination and adjustment between the raw materials, the lamellar montmorillonite is coordinated with the flaky talc, and the a-alumina is adjusted at the same time, as well as the dopamine hydrochloride solution and the sodium carboxymethyl cellulose. The synergistic effect of the talc-modified conditioning agent obtained by the coordination between the raw materials and the linking and balancing agent is enhanced, so that the performance of the product is further improved. DETAILED DESCRIPTION

[0030] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The natural stone thermal insulation and decorative integrated board based on foamed ceramics of this embodiment comprises a base layer and a finishing layer. The finishing layer has a decorative pattern on its surface for decorating the base layer. The base layer comprises the following raw materials in parts by weight:

[0032] 25-30 parts of quartz, 10-15 parts of clay, 8-12 parts of fly ash, 7-11 parts of linking and balancing agents, 6-9 parts of talcum powder modified conditioning agent, 5-8 parts of glass beads, 4-7 parts of flame retardant, 2-4 parts of dispersant, 1-3 parts of foaming agent, and 20-25 parts of deionized water.

[0033] The natural stone thermal insulation decorative integrated board of this embodiment includes the following raw materials in parts by weight:

[0034] 27.5 parts of quartz, 12.5 parts of clay, 10 parts of fly ash, 9 parts of linking and balancing agent, 7.5 parts of talcum powder modified conditioning agent, 6.5 parts of glass beads, 5.5 parts of flame retardant, 3 parts of dispersant, 2 parts of foaming agent, and 22.5 parts of deionized water.

[0035] The dispersant in this embodiment is sodium lignin sulfonate; the foaming agent is silicon carbide; and the flame retardant is magnesium hydroxide.

[0036] The preparation method of the linking and balancing agent of this embodiment is:

[0037] S01: adding nano-yttrium oxide to a 5% chitosan solution with a mass fraction of 2 to 5 times the total amount of nano-yttrium oxide, and then adding a 4% sodium silicate solution with a mass fraction of 5 to 8% of the total amount of nano-yttrium oxide, stirring thoroughly to obtain an additive solution;

[0038] S02: The mesoporous silica is added to a sufficient amount of a 5% by mass sulfuric acid solution and stirred sufficiently, then washed with water and dried, and the dried mesoporous silica and the additive solution are stirred sufficiently in a weight ratio of 2:5 to obtain a mesoporous silica liquid;

[0039] S03: The mesoporous silica liquid and the linking and balancing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the linking and balancing agent.

[0040] The particle size of the mesoporous silica in this embodiment is between 70 and 80 nm, and the pore size is between 15 and 20 nm.

[0041] The preparation method of the balancing agent of this embodiment is:

[0042] 4 to 7 parts of glass fiber, 1 to 3 parts of stearic acid and 5 to 8 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent;

[0043] 3-5 parts of boron nitride agent are added into 5-8 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

[0044] The preparation method of the talcum powder modified toner of this embodiment is as follows:

[0045] S01: Stir talc powder thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry, stir the dried talc powder thoroughly in a sodium citrate solution of 3 to 5 times the total amount of the dried talc powder to obtain a talc powder liquid;

[0046] S02: 5 to 8 parts of talc liquid, 2 to 4 parts of silane coupling agent KH550, 1 to 3 parts of sodium hexametaphosphate and 1 to 2 parts of 5% by mass sodium lignin sulfonate solution are fully blended to obtain a talc blending agent;

[0047] S03: adding 3-5 parts of a-alumina and 2-3 parts of montmorillonite powder to 5-8 parts of dopamine hydrochloride solution, and then adding 1-2 parts of sodium carboxymethyl cellulose for ultrasonic treatment, and then filtering and drying to obtain a-alumina-montmorillonite property-adjusting hybrid agent;

[0048] S04: The talcum powder conditioning agent and the α-alumina-montmorillonite conditioning hybrid agent are mixed and ball-milled in a weight ratio of 5:(2-3) at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the conditioning agent modified by the talcum powder is filtered and dried to obtain.

[0049] The mass fraction of the sodium citrate solution in this embodiment is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

[0050] The ultrasonic power of the ultrasonic treatment in this embodiment is 450-500W, and the ultrasonic time is 15-20min.

[0051] A method for preparing a natural stone thermal insulation and decorative integrated board based on foamed ceramics in this embodiment includes the following steps:

[0052] The raw materials in the base layer are mixed and ball-milled thoroughly at a mixing speed of 1500r / min for 1h, and then put into a mold for pressing at a pressing pressure of 10-15MPa for 20min. After the pressing is completed, the mold is demoulded to obtain a green body, and the green body is sintered at 1150-1170℃ for 2h. After the sintering is completed, the base layer is obtained, and then the surface of the base layer is decorated with a pattern to form a finishing layer to obtain the thermal insulation decorative integrated board of the present invention.

[0053] Example 1.

[0054] The natural stone thermal insulation and decorative integrated board based on foamed ceramics of this embodiment comprises a base layer and a finishing layer. The finishing layer has a decorative pattern on its surface for decorating the base layer. The base layer comprises the following raw materials in parts by weight:

[0055] 25 parts of quartz, 10 parts of clay, 8 parts of fly ash, 7 parts of linking and balancing agent, 6 parts of talcum powder modified conditioning agent, 5 parts of glass microspheres, 4 parts of flame retardant, 2 parts of dispersant, 1 part of foaming agent, and 20 parts of deionized water.

[0056] The dispersant in this embodiment is sodium lignin sulfonate; the foaming agent is silicon carbide; and the flame retardant is magnesium hydroxide.

[0057] The preparation method of the linking and balancing agent of this embodiment is:

[0058] S01: adding nano-yttrium oxide to a 5% chitosan solution having a mass fraction of 2 times the total amount of nano-yttrium oxide, and then adding a 4% sodium silicate solution having a mass fraction of 5% of the total amount of nano-yttrium oxide, stirring sufficiently to obtain an additive solution;

[0059] S02: The mesoporous silica is added to a sufficient amount of a 5% by mass sulfuric acid solution and stirred sufficiently, then washed with water and dried, and the dried mesoporous silica and the additive solution are stirred sufficiently in a weight ratio of 2:5 to obtain a mesoporous silica liquid;

[0060] S03: The mesoporous silica liquid and the linking and balancing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the linking and balancing agent.

[0061] The particle size of the mesoporous silica in this embodiment is between 70 nm and the pore size is between 15 nm.

[0062] The preparation method of the balancing agent of this embodiment is:

[0063] 4 parts of glass fiber, 1 part of stearic acid and 5 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent;

[0064] 3 parts of boron nitride agent are added into 5 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

[0065] The preparation method of the talcum powder modified toner of this embodiment is as follows:

[0066] S01: Stir talc powder thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry, stir the dried talc powder thoroughly in a sodium citrate solution of 3 times the total amount of the dried talc powder to obtain a talc powder liquid;

[0067] S02: 5 parts of talc liquid, 2 parts of silane coupling agent KH550, 1 part of sodium hexametaphosphate and 1 part of 5% by mass sodium lignin sulfonate solution are fully blended to obtain a talc blending agent;

[0068] S03: adding 3 parts of α-alumina and 2 parts of montmorillonite powder to 5 parts of dopamine hydrochloride solution, and then adding 1 part of sodium carboxymethyl cellulose for ultrasonic treatment, and then filtering and drying to obtain α-alumina-montmorillonite property-adjusting hybrid agent;

[0069] S04: The talcum powder conditioning agent and the α-alumina-montmorillonite conditioning hybrid agent are mixed in a weight ratio of 5:2 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a conditioning agent modified with the talcum powder.

[0070] The mass fraction of the sodium citrate solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 3%.

[0071] The ultrasonic power of the ultrasonic treatment in this embodiment is 450W, and the ultrasonic time is 15min.

[0072] A method for preparing a natural stone thermal insulation and decorative integrated board based on foamed ceramics in this embodiment includes the following steps:

[0073] The raw materials in the base layer are mixed and ball-milled thoroughly at a mixing speed of 1500r / min for 1h, and then put into a mold for pressing at a pressing pressure of 10MPa for 20min. After the pressing is completed, the mold is demoulded to obtain a green body, and the green body is sintered at 1150°C for 2h. After the sintering is completed, the base layer is obtained, and then the surface of the base layer is decorated with a pattern to form a finishing layer to obtain the thermal insulation decorative integrated board of the present invention.

[0074] Example 2.

[0075] The natural stone thermal insulation and decorative integrated board based on foamed ceramics of this embodiment comprises a base layer and a finishing layer. The finishing layer has a decorative pattern on its surface for decorating the base layer. The base layer comprises the following raw materials in parts by weight:

[0076] 30 parts of quartz, 15 parts of clay, 12 parts of fly ash, 11 parts of linking and balancing agent, 9 parts of talcum powder modified conditioning agent, 8 parts of glass beads, 7 parts of flame retardant, 4 parts of dispersant, 3 parts of foaming agent, and 25 parts of deionized water.

[0077] The dispersant in this embodiment is sodium lignin sulfonate; the foaming agent is silicon carbide; and the flame retardant is magnesium hydroxide.

[0078] The preparation method of the linking and balancing agent of this embodiment is:

[0079] S01: adding nano-yttrium oxide to a 5% chitosan solution with a mass fraction of 5 times the total amount of nano-yttrium oxide, and then adding a 4% sodium silicate solution with a mass fraction of 8% of the total amount of nano-yttrium oxide, stirring thoroughly to obtain an additive solution;

[0080] S02: The mesoporous silica is added to a sufficient amount of a 5% by mass sulfuric acid solution and stirred sufficiently, then washed with water and dried, and the dried mesoporous silica and the additive solution are stirred sufficiently in a weight ratio of 2:5 to obtain a mesoporous silica liquid;

[0081] S03: The mesoporous silica liquid and the linking and balancing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the linking and balancing agent.

[0082] The particle size of the mesoporous silica in this embodiment is between 80 nm and the pore size is between 20 nm.

[0083] The preparation method of the balancing agent of this embodiment is:

[0084] 7 parts of glass fiber, 3 parts of stearic acid and 8 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent;

[0085] 5 parts of boron nitride agent are added into 8 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

[0086] The preparation method of the talcum powder modified toner of this embodiment is as follows:

[0087] S01: Stir talc powder thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry, and stir the dried talc powder thoroughly in a sodium citrate solution of 5 times the total amount of the dried talc powder to obtain a talc powder liquid;

[0088] S02: 8 parts of talc liquid, 4 parts of silane coupling agent KH550, 3 parts of sodium hexametaphosphate and 2 parts of 5% by mass sodium lignin sulfonate solution are fully blended to obtain a talc blending agent;

[0089] S03: adding 5 parts of α-alumina and 3 parts of montmorillonite powder to 8 parts of dopamine hydrochloride solution, and then adding 2 parts of sodium carboxymethyl cellulose for ultrasonic treatment, and then filtering and drying to obtain α-alumina-montmorillonite property-adjusting hybrid agent;

[0090] S04: The talcum powder conditioning agent and the α-alumina-montmorillonite conditioning hybrid agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a conditioning agent modified with the talcum powder.

[0091] The mass fraction of the sodium citrate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 6%.

[0092] The ultrasonic power of the ultrasonic treatment in this embodiment is 500W, and the ultrasonic time is 20min.

[0093] A method for preparing a natural stone thermal insulation and decorative integrated board based on foamed ceramics in this embodiment includes the following steps:

[0094] The raw materials in the base layer are mixed and ball-milled thoroughly at a mixing speed of 1500r / min for 1h, and then put into a mold for pressing at a pressing pressure of 15MPa for 20min. After the pressing is completed, the mold is demoulded to obtain a green body, and the green body is sintered at 1170°C for 2h. After the sintering is completed, the base layer is obtained, and then the surface of the base layer is decorated with a pattern to form a finishing layer to obtain the thermal insulation decorative integrated board of the present invention.

[0095] Example 3.

[0096] The natural stone thermal insulation and decorative integrated board based on foamed ceramics of this embodiment comprises a base layer and a finishing layer. The finishing layer has a decorative pattern on its surface for decorating the base layer. The base layer comprises the following raw materials in parts by weight:

[0097] 27.5 parts of quartz, 12.5 parts of clay, 10 parts of fly ash, 9 parts of linking and balancing agent, 7.5 parts of talcum powder modified conditioning agent, 6.5 parts of glass beads, 5.5 parts of flame retardant, 3 parts of dispersant, 2 parts of foaming agent, and 22.5 parts of deionized water.

[0098] The dispersant in this embodiment is sodium lignin sulfonate; the foaming agent is silicon carbide; and the flame retardant is magnesium hydroxide.

[0099] The preparation method of the linking and balancing agent of this embodiment is:

[0100] S01: adding nano-yttrium oxide to a 5% chitosan solution with a mass fraction of 3.5 times the total amount of nano-yttrium oxide, and then adding a 4% sodium silicate solution with a mass fraction of 6.5% of the total amount of nano-yttrium oxide, stirring thoroughly, and obtaining an additive solution;

[0101] S02: The mesoporous silica is added to a sufficient amount of a 5% by mass sulfuric acid solution and stirred sufficiently, then washed with water and dried, and the dried mesoporous silica and the additive solution are stirred sufficiently in a weight ratio of 2:5 to obtain a mesoporous silica liquid;

[0102] S03: The mesoporous silica liquid and the linking and balancing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the linking and balancing agent.

[0103] The particle size of the mesoporous silica in this embodiment is between 75 nm and the pore size is between 17.5 nm.

[0104] The preparation method of the balancing agent of this embodiment is:

[0105] 5.5 parts of glass fiber, 2 parts of stearic acid and 6.5 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent;

[0106] 4 parts of boron nitride agent were added into 6.5 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

[0107] The preparation method of the talcum powder modified toner of this embodiment is as follows:

[0108] S01: Stir talc powder thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry, stir the dried talc powder thoroughly in a sodium citrate solution of 4 times the total amount of the dried talc powder to obtain a talc powder liquid;

[0109] S02: 6.5 parts of talc liquid, 3 parts of silane coupling agent KH550, 2 parts of sodium hexametaphosphate and 1.5 parts of 5% by mass sodium lignin sulfonate solution are fully blended to obtain a talc blending agent;

[0110] S03: 4 parts of α-alumina and 2.5 parts of montmorillonite powder are added to 6.5 parts of dopamine hydrochloride solution, and then 1.5 parts of sodium carboxymethyl cellulose are added for ultrasonic treatment, and then filtered and dried to obtain an α-alumina-montmorillonite hybrid agent;

[0111] S04: The talcum powder conditioning agent and the α-alumina-montmorillonite conditioning hybrid agent are mixed in a weight ratio of 5:2.5, and the mixture is ball-milled at a speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain a conditioning agent modified with the talcum powder.

[0112] The mass fraction of the sodium citrate solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 4.5%.

[0113] The ultrasonic power of the ultrasonic treatment in this embodiment is 470W, and the ultrasonic time is 17.5min.

[0114] A method for preparing a natural stone thermal insulation and decorative integrated board based on foamed ceramics in this embodiment includes the following steps:

[0115] The raw materials in the base layer are mixed and ball-milled thoroughly at a mixing speed of 1500r / min for 1h, and then put into a mold for pressing at a pressing pressure of 12.5MPa for 20min. After the pressing is completed, the mold is demoulded to obtain a green body, and the green body is sintered at 1160°C for 2h. After the sintering is completed, the base layer is obtained, and then the surface of the base layer is decorated with a pattern to form a finishing layer to obtain the thermal insulation decorative integrated board of the present invention.

[0116] Comparative Example 1.

[0117] The difference from Example 3 is that no linking agent or equalizing agent is added.

[0118] Comparative Example 2.

[0119] The difference from Example 3 is that no mesoporous silica liquid is added in the preparation of the linking and balancing agent.

[0120] Comparative Example 3.

[0121] The difference from Example 3 is that no additive liquid is added to the mesoporous silica liquid.

[0122] Comparative Example 4.

[0123] The difference from Example 3 is that no linking agent is added during the preparation of the linking and balancing agent.

[0124] Comparative Example 5.

[0125] Different from Example 3, no talcum powder modified toner was added.

[0126] Comparative Example 6.

[0127] The difference from Example 3 is that no talcum powder conditioning agent is added in the preparation of the talcum powder modified conditioning agent.

[0128] Comparative Example 7.

[0129] The difference from Example 3 is that no talcum powder liquid is added in the preparation of the talcum powder blending agent.

[0130] Comparative Example 8.

[0131] The difference from Example 3 is that no α-alumina-montmorillonite hybridizing agent is added in the preparation of the talc-modified conditioning agent.

[0132] Comparative Example 9.

[0133] The difference from Example 3 is that α-alumina and sodium carboxymethyl cellulose are not added in the preparation of the α-alumina-montmorillonite property-adjusting hybrid agent.

[0134] Comparative Example 10.

[0135] The difference from Example 3 is that in the preparation of the α-alumina-montmorillonite hybrid agent, the montmorillonite powder and the dopamine hydrochloride solution are replaced by water.

[0136] Conventional test, testing the thermal insulation, impact resistance and fire resistance of Examples 1 to 3 and Comparative Examples 1 to 10, and testing the water resistance, acid corrosion and cold and hot cycle stability of the products, soaking the products in room temperature water for 12 hours, then placing them under 2% hydrochloric acid mist conditions for 6 hours, then heat treating them at 65°C for 12 hours, and then treating them at -5°C for 12 hours, the above is one cycle, and the cycle test is repeated 10 times;

[0137]

[0138] It can be seen from Comparative Examples 1 to 10 and Examples 1 to 3 that;

[0139] The product of Example 3 has excellent thermal insulation, impact resistance and fire resistance, and the product has excellent performance stability under conditions of water resistance, acid corrosion and cold and hot cycle;

[0140] From Comparative Examples 1 to 10 and Example 3, it can be seen that the performance of the product is significantly deteriorated when the Lianhe Hengxue agent and the talc modified toner are not added to the product. The Lianhe Hengxue agent is used in combination with the talc modified toner, and the two are synergistically matched to enhance the performance of the product.

[0141] The performance of the products showed a trend of varying degrees of deterioration when no mesoporous silica liquid was added to the preparation of the Lianhe balance agent, no additive liquid was added to the mesoporous silica liquid, and no Lianhe balance agent was added to the preparation of the Lianhe balance agent. The Lianhe balance agent obtained by the method of the present invention had the most significant product performance effect. The Lianhe balance agent was not added to the preparation of the Lianhe balance agent, and the performance of the product also showed a relatively obvious trend of deterioration.

[0142] In the preparation of the blended talc modified conditioning agent, no talc conditioning agent is added, no talc liquid is added, no α-alumina-montmorillonite conditioning hybrid agent is added, no α-alumina and sodium carboxymethyl cellulose are added, and montmorillonite powder and dopamine hydrochloride solution are replaced by water in the preparation of the α-alumina-montmorillonite conditioning hybrid agent. The performance of the products has a tendency to deteriorate to varying degrees. The blended talc modified conditioning agent obtained by combining the α-alumina-montmorillonite conditioning hybrid agent obtained by the specific method of the present invention with the talc conditioning agent has the most significant product performance effect, and the replacement by other methods is not as obvious as the effect of the present invention.

[0143] The present invention further explores the product performance through the preparation of the balancing agent;

[0144] The preparation method of the balancing agent is:

[0145] 5.5 parts of glass fiber, 2 parts of stearic acid and 6.5 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent;

[0146] 4 parts of boron nitride agent were added into 6.5 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

[0147] Experimental example 1.

[0148] The same as Example 3, except that no boron nitride agent was added during the preparation of the balancing agent.

[0149] Experimental example 2.

[0150] Same as in Example 3, the boron nitride agent is directly replaced by the boron nitride raw material.

[0151] Experimental Example 3.

[0152] The same as Example 3, the only difference is that no glass fiber liquid is added in the preparation of the balancing agent.

[0153] Experimental Example 4.

[0154] The same as Example 3, the only difference is that no glass fiber is added to the glass fiber liquid.

[0155] Experimental Example 5.

[0156] The same as Example 3, except that stearic acid is not added to the glass fiber solution and water is used instead of the lanthanum nitrate solution.

[0157] The performance test results of Examples 1-5 are as follows:

[0158]

[0159] It can be seen from Experimental Examples 1-5 that when no boron nitride agent and no glass fiber liquid were added in the preparation of the balancing agent, the performance of the product deteriorated significantly. Secondly, when no glass fiber was added to the glass fiber liquid, the boron nitride agent was directly replaced by boron nitride raw material, and stearic acid was not added to the glass fiber liquid, and the lanthanum nitrate solution was replaced by water, the performance of the product tended to deteriorate. Only when the boron nitride agent prepared by the method of the present invention was combined with raw materials such as glass fiber liquid, the performance effect of the product was the most significant. When other methods were used as substitutes, the effects were not as significant as those of the present invention. In addition, the glass fiber liquid and the boron nitride agent of the present invention are unique, and the technical effects of the present invention cannot be achieved by using other methods as substitutes.

[0160] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0161] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A natural stone thermal insulation decorative integrated board based on foamed ceramics, comprising a base layer and a facing layer, wherein the facing layer has a decorative pattern on its surface and is used to decorate the base layer, characterized in that: The base layer comprises the following raw materials in parts by weight: 25-30 parts of quartz, 10-15 parts of clay, 8-12 parts of fly ash, 7-11 parts of linking and balancing agents, 6-9 parts of talcum powder modified conditioning agent, 5-8 parts of glass beads, 4-7 parts of flame retardant, 2-4 parts of dispersant, 1-3 parts of foaming agent, and 20-25 parts of deionized water.

2. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 1, characterized in that: The natural stone thermal insulation decorative integrated board comprises the following raw materials in parts by weight: 27.5 parts of quartz, 12.5 parts of clay, 10 parts of fly ash, 9 parts of linking and balancing agent, 7.5 parts of talcum powder modified conditioning agent, 6.5 parts of glass beads, 5.5 parts of flame retardant, 3 parts of dispersant, 2 parts of foaming agent, and 22.5 parts of deionized water.

3. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 1, characterized in that: The dispersant is sodium lignin sulfonate; the foaming agent is silicon carbide; and the flame retardant is magnesium hydroxide.

4. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 1, characterized in that: The preparation method of the linking and balancing agent is as follows: S01: adding nano-yttrium oxide to a 5% chitosan solution with a mass fraction of 2 to 5 times the total amount of nano-yttrium oxide, and then adding a 4% sodium silicate solution with a mass fraction of 5 to 8% of the total amount of nano-yttrium oxide, stirring thoroughly to obtain an additive solution; S02: The mesoporous silica is added to a sufficient amount of a 5% by mass sulfuric acid solution and stirred sufficiently, then washed with water and dried, and the dried mesoporous silica and the additive solution are stirred sufficiently in a weight ratio of 2:5 to obtain a mesoporous silica liquid; S03: The mesoporous silica liquid and the linking and balancing agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the linking and balancing agent.

5. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 4, characterized in that: The particle size of the mesoporous silica is between 70 and 80 nm, and the pore size is between 15 and 20 nm.

6. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 4, characterized in that: The preparation method of the balancing agent is: 4 to 7 parts of glass fiber, 1 to 3 parts of stearic acid and 5 to 8 parts of 5% by mass lanthanum nitrate solution are fully mixed to obtain a glass fiber solution; boron nitride and 6% by mass zinc nitrate solution are stirred evenly in a weight ratio of 2:5 to obtain a boron nitride agent; 3-5 parts of boron nitride agent are added into 5-8 parts of glass fiber liquid and stirred thoroughly, then filtered and dried to obtain a balancing agent.

7. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 1, characterized in that: The preparation method of the talcum powder modified conditioning agent is as follows: S01: Stir talc powder thoroughly in a sufficient amount of 5% by mass hydrogen peroxide solution, then wash, filter and dry, stir the dried talc powder thoroughly in a sodium citrate solution of 3 to 5 times the total amount of the dried talc powder to obtain a talc powder liquid; S02: 5 to 8 parts of talc liquid, 2 to 4 parts of silane coupling agent KH550, 1 to 3 parts of sodium hexametaphosphate and 1 to 2 parts of 5% by mass sodium lignin sulfonate solution are fully blended to obtain a talc blending agent; S03: adding 3-5 parts of a-alumina and 2-3 parts of montmorillonite powder to 5-8 parts of dopamine hydrochloride solution, and then adding 1-2 parts of sodium carboxymethyl cellulose for ultrasonic treatment, and then filtering and drying to obtain a-alumina-montmorillonite property-adjusting hybrid agent; S04: The talcum powder conditioning agent and the α-alumina-montmorillonite conditioning hybrid agent are mixed and ball-milled in a weight ratio of 5:(2-3) at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the conditioning agent modified by the talcum powder is filtered and dried to obtain.

8. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 7, characterized in that: The mass fraction of the sodium citrate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

9. The natural stone thermal insulation and decorative integrated board based on foamed ceramics according to claim 7, characterized in that: The ultrasonic power of the ultrasonic treatment is 450-500W, and the ultrasonic time is 15-20min.

10. A method for preparing a natural stone thermal insulation and decorative integrated board based on foamed ceramics as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials in the base layer are mixed and ball-milled thoroughly at a mixing speed of 1500r / min for 1h, and then put into a mold for pressing at a pressing pressure of 10-15MPa for 20min. After the pressing is completed, the mold is demoulded to obtain a green body, and the green body is sintered at 1150-1170℃ for 2h. After the sintering is completed, the base layer is obtained, and then the surface of the base layer is decorated with a pattern to form a finishing layer to obtain the thermal insulation decorative integrated board of the present invention.

Citation Information

Patent Citations

  • Silicon dioxide-modified porous zirconium oxide ceramic and preparation method thereof

    CN106830962A

  • Cement-imitated wood and preparation method thereof

    CN107572972A

  • Environment-friendly thermal-insulation decorative foamed ceramic plate and preparation method thereof

    CN115160014A

  • Sound insulation foam wallboard and preparation method thereof

    CN116161911A

  • Modified forsterite spinel brick for regenerative chamber

    CN116874309A

Cited By

  • Explosion-proof heat-insulating glass and preparation method thereof

    CN120965116A

  • Enhanced polymethacrylimide foam composite material and preparation method thereof

    CN121159759A